Planos de melhora do sistema de qualidade na gestão escolar: experiência de um Colégio da Rede Jesuíta de Educação - Souza, Anderson Rafael da Silva (Universidade do Vale do Rio dos Sinos, 2021)
This Master thesis in Educational Management aims to analyze plans to improve the Quality System School Management (SQGE). The research took place at Colégio Antônio Vieira, in Salvador, an institution that is part of the Jesuit Education Network (RJE). The methodology was of qualitative nature, using document analysis techniques, semi-structured interviews with 1st Grade High School teachers and management team, high school student questionnaires and participant observation. In the content analysis, the following aspects emerged: teachers’ reflection on their practice, formative guidelines as a way to find methodological paths, student training engagement and the role of each person. Although the school has presented satisfactory answers to the research problem, there are some possibilities for advances after finishing the investigative work, that is why the intervention and collaboration proposal : teachers’ , students’ and management team engagement with a monitoring plan, students’ involvement in the second SQGE evaluation cycle, constant analysis of students’ academic performance in order to find ways to improve learning.
Keywords: Sistema de qualidade; Gestão escolar; Processo de aprendizagem; Planos de melhora; Quality system; School management; Learning process; Improvement plans; ACCNPQ::Ciências Humanas::Educação